Советский ренессанс и шестидесятники (размышления о поэзии русских и азербайджанских шестидесятников - Касымов, Я. (Культура народов Причерноморья, 2014)
В статье «Советский ренессанс и шестидесятники» рассматривается своеобразие
поэтического процесса 1960-х годов. В этой связи данная проблема впервые рассматривается через
призму творчества молодого поколения литераторов. Предпринимается попытка обобщения
произведений в контексте советской литературы. По этой причине в процессе исследования имеют
место ссылки на поэзию таких известных азербайджанских и русских шестидесятников, как А. Керим,
М. Араз, Х. Улутюрк, В. Самедоглы, Ф. Годжа, а также Е. Евтущенко, А. Вознесенский, Б. Ахмадулина,
Р. Рождественкий, Н. Рубцова и т.д. Освещаются основные контуры творческих идеалов нового
поколения литераторов. Здесь также анализируются поэтический генезис поколения литераторов,
поэтические истоки шестидесятников. Отмечается, что эти литераторы были непосредственными
продолжателями традиции корифеев поэзии ХХ века. Подчеркивается историческая закономерность
поэтических сочинений молодых поэтов, а также делается акцент на незыблемость духовных связей
между поколениями. Таким образом, нами прослеживается траектория художественного развития в
описании шестидесятниками жизненных и природных коллизий, усовершенствование ими анализа при
изображении общественных контрастов. Любопытно, что именно шестидесятники были первыми,
кто обрекся от нетрадиционных и далёких от национальной сущности категории, как родина, народ,
духовное существо, национальное прошлое и будущее, национальная история и т.д.
Здесь также прослеживается процесс зарождения и эстетического фиаско культа поэтического «мы»,
что повлекло за собой изменения, эстетические преломления в системе образов. В действительности,
художественные системы, зародившиеся на основе лирического «мы» и лирического «я» коренным
образом отличаются друг от друга. В ходе изучения настоящей проблемы автором делаются попытки
сравнительного анализа и обобщения процесса зарождения, падения культа поэтического «мы»,
возникновения эстетического комплекса лирического «я». Детально исследуются этапы формирования
и особенности нового трагического стиля. Для этого используются ссылки на стихи авторов,
относящихся к плеяде упомянутого периода. На основе поэтических примеров подчеркивается
самобытность данного процесса. Обобщаются незыблемые художественные заслуги шестидесятников
в процессе прогресса национально-эстетического мышления, даётся общая оценка поэтическим
течениям 1960-80-х годов. У статті «Радянський ренесанс і шістдесятники» розглядається своєрідність поетичного
процесу 1960-х років. У цьому зв'язку дана проблема:, яка вперше розглядається через призму творчості
молодого покоління літераторів. Робиться спроба узагальнення творів в контексті радянської
літератури. З цієї причини в процесі дослідження важливе місце займають посилання на поезію таких
відомих азербайджанських і російських шістдесятників, як А. Керім, М. Араз, Х. Улутюрк, В. Самедогли,
Ф. Годжа, а також Є. Евтущенко, А. Вознесенский, Б. Ахмадуліна, Р. Рождественкий, Н. Рубцова і т.д.
Висвітлюються основні контури творчих ідеалів нового покоління літераторів. Тут також
аналізуються поетичний генезис покоління літераторів, поетичні витоки шістдесятників.
Відзначається, що ці літератори були безпосередніми продовжувачами традиції корифеїв поезії ХХ
століття. Підкреслюється історична закономірність поетичних творів молодих поетів, а також
робиться акцент на непорушність духовних зв'язків між поколіннями. Таким чином, нами
простежується траєкторія художнього розвитку в описі шістдесятниками життєвих та природних
колізій, удосконалення ними аналізу при зображенні громадських контрастів. Цікаво, що саме
шістдесятники були першими, хто прирік себе від нетрадиційних і далеких від національної сутності
категорії, як батьківщина, народ, духовна істота, національне минуле і майбутнє, національна історія і
т.д.
Безпосередньо простежується процес зародження і естетичного фіаско культу поетичного «ми», що
спричинило за собою зміни, естетичні заломлення в системі образів. В дійсності, художні системи, які
зародилися на основі ліричного «ми» і ліричного «я» корінним чином відрізняються один від одного. В
ході вивчення цієї проблеми автор робить спроби порівняльного аналізу і узагальнення процесу
зародження, падіння культу поетичного «ми», виникнення естетичного комплексу ліричного «я».
Детально досліджуються етапи формування та особливості нового трагічного стилю. Для цього
використовуються посилання на вірші авторів, що відносяться до плеяди згаданого періоду. На основі
поетичних прикладів підкреслюється самобутність даного процесу. Узагальнюються непорушні
художні заслуги шістдесятників в процесі прогресу національно-естетичного мислення, дається
загальна оцінка поетичним течіям 1960-80-х років. The article “Soviet Renaissance and sixtieths” underlines peculiarity of the poetic process in 60s and
that this problem is for the first time generalized in this research work based on general creativity of literary
generation. For this reason reference to works of the prominent Russian sixtyths like Yevg.Yevtushenko,
A.Voznesenski, B.Akhmadulina, R.Rojdenstvenski, N.Rubtsov alongside with the prominent Azerbaijani sixtyths
A. Kerim, M. Araz, Kh.R.Uluturk, F.Goja, V.Samadoglu and others are grounded in this research work.
Poetic manifests and literary desires of Azerbaijani and Uzbek sixtieth are analyzed in the first chapter titled
“New poetic ideas of the sixtieths”. Main contours of poetic ideal are shown in the poems “My poem”, “Poem
of mine”, “Poet”, “Poetry”, “Poetry” which belong to the pen of young poets. The article speaks about the
origin of sixtieths and their being direct followers of such masters of 20th century. Tens of young sixtieths poems,
dedicated to these literary figures, obviously exhibit unbreakability of spiritual relations between the generations. Evolution of the aesthetics world outlook of young generation is reflected in the poems describing
relations between human and nature, nature and seasons of human life. Thus we observe the movement of poetic
thinking from description of live and natural contrast towards analysis of social reality in the first lyrics of the
young sixtieths.
One of the main problems conditioning artistic peculiarity of new generation in the fifth chapter titled “New
location of poetic thought” is process of transition from Political-Geographical Motherland to National
Motherland, in other words, from Ideal-Political Motherland to Native Real Motherland, lighted in the works of
the brightest representatives of two brother poetry. The conception of New Motherland, evidenced in the lyrics of
such grand talents as A. Kerim, M.Araz, Kh.R.Uluturk are analyzed based on characteristic samples.
In the article is analyzed total change of the attitude to aesthetic understanding and categories existing in
literature in the result of transition to the system of new imaginative comprehension and strengthening of newly
qualified aesthetic principles in poetic creativity. Young sixtieths firstly rejected such notions of non-traditional
and non-national aesthetic content such as Motherland, People, moral unity, national past and future, history
etc. as well as an absurd and an abstract notion of ‘Soviet people’. Establishment of poetic ‘we’ cult and its
aesthetic break-up, changes took place in the system of image on this basis, aesthetic revolutions and other
scientific problems are analyzed in the sixth chapter titled ‘Aesthetic changes of main lyrical image’ Artistic
systems founded on lyric ‘we’ and lyric ‘I’ differ from each-other to serious extend; establishment, break-up of
poetic ‘we’ cult, emergence of lyrical ‘I’ aesthetic complex is generalized on the ground of comparative analysis.
One of important innovations enlivened by plead and brought to poetry – putting an end to 40 years dictatorship
of joy and happiness, unnatural carelessness - are examined in the article. Stages of formation and
specifications of new tragic style, based on analysis of tens of big poems written by the plead, are deeply
analyzed in the book and specifications of this process are described via specific examples. Not only unrepeated
artistic services of the poetic process of 60-80s, and of the sixtieths in particular, in growth of national-aesthetic
thinking, but also its role and position in improvement of national and humanist thinking are generalized in the
article based on ideas and views of the prominent representatives of universal theoretical-aesthetic thought. The
article definitely shows innovations brought by the sixtieths to their culture of national poetry and the system of
artistic thinking, their main artistic reforms and revolutionary changes they apply bravely in literary life based
on separate scientific-aesthetic provisions and generalized synopsis. It also underlines that enlivening of
traditions in national-artistic thinking by the sixtieth, joining the ties between literary era and generations and
restoration of thousand year long connection are among the most of their important inputs and services.